Antibacterial activity of synthesized 2,4,5-trisubstituted imidazole derivatives - Khan, Mohd Sajid; Siddiqui, Shafi Ahmad; Siddiqui, Mohammad Shaik Rafi Ahmad; Goswami, Usha; Srinivasan, Kumar Venkatraman; Khan, Mohammad Islam (Chemical Biology & Drug Design, 2008)
Some novel chemically synthesized 2,4,5-trisubstituted imidazoles from aryl aldehydes and 1,2-diketones or alpha-hydroxyketone were screened against eight different human pathogenic bacteria and fungi. Seven compounds were found to be active against different bacteria. These compounds showed variation in activity and were found to be active against Gram-positive as well as Gram-negative bacteria. Compound 4-(4,5-diphenyl-1H-imidazol-2-yl)-phenol, 3d was the only compound which showed activity against Klebsiella pneumoniae while rest of the compounds did not show significant activity against this micro-organism. Minimum inhibitory concentrations of the compounds were in the range of 0.50 to 6.1 mu g/mL and minimum bactericidal concentration ranges from 1.11 to 12.9 mu g/mL. The candidature of active compounds to be an effective and novel drug was examined based on Lipinski's rule of Five which explained ClogP, LogS, H-bond acceptors, H-Bond donors and rotational bonds. Compounds 3a-d and 3f satisfies Lipinski's rule of Five and could be proposed as potent new antibacterial drugs.
Keywords: 1; 2; 2-Diketones; 4; 5-trisubstituted imidazoles; alpha-hydroxyketone; antibacterial activity; aryl aldehydes

Design, synthesis, evaluation and thermodynamics of 1-substituted pyridylimidazo[1,5-a]pyridine derivatives as cysteine protease inhibitors - Khan, Mohd Sajid; Baig, Mohd Hassan; Ahmad, Saheem; Siddiqui, Shapi Ahmad; Srivastava, Ashwini Kumar; Srinivasan, Kumar Venkatraman; Ansari, Irfan A. (Plos One, 2013)
Targeting papain family cysteine proteases is one of the novel strategies in the development of chemotherapy for a number of diseases. Novel cysteine protease inhibitors derived from 1-pyridylimidazo[1,5-a]pyridine representing pharmacologically important class of compounds are being reported here for the first time. The derivatives were initially designed and screened in silico by molecular docking studies against papain to explore the possible mode of action. The molecular interaction between the compounds and cysteine protease (papain) was found to be very similar to the interactions observed with the respective epoxide inhibitor (E-64c) of papain. Subsequently, compounds were synthesized to validate their efficacy in wet lab experiments. When characterized kinetically, these compounds show their K-i and IC50 values in the range of 13.75 to 99.30 mu M and 13.40 to 96.50 mu M, respectively. The thermodynamics studies suggest their binding with papain hydrophobically and entropically driven. These inhibitors also inhibit the growth of clinically important different types of Gram positive and Gram negative bacteria having MIC50 values in the range of 0.6-1.4 mu g/ml. Based on Lipinski's rule of Five, we also propose these compounds as potent antibacterial prodrugs. The most active antibacterial compound was found to be 1-(2-pyridyl)-3-(2-hydroxyphenyl)imidazo[1,5-a]pyridine (3a).